Factors influencing consumer satisfaction toward Vinhomes Riverside’s terrace houses - Duong, Thi Thanh Hoa (Khoa Quốc tế, ĐHQGHN, 2019)
Customer satisfaction represents a modern approach for quality in enterprises and organizations and serves the development of a truly customer-focused management and culture. Measuring customer satisfaction offers an immediate, meaningful and objective feedback about clients’ preferences and expectations. In this way, company’s performance may be evaluated in relation to a set of satisfaction dimensions that indicate the strong and the weak points of a business organization. This thesis presents an original customer satisfaction survey toward Vinhomes Riverside’ terraced houses. Specifically, the study focuses on technical quality, functional quality and warranty services and builder’s readiness to cooperate. After collecting information from Vinhomes Riverside’ resident, I would utilize descriptive statistical, comparative and forecasting method to analyze the advantages and disadvantages of Vinhomes in fulfillment and remaining customers.